El català a l'escola de Mallorca - Melià i Garí, Joan (Caplletra. Revista Internacional de Filologia, 1996)
The author presents schools as an overestimated socialization environment, which nowadays has to compete with the media. There is special emphasis on the relatively limited influence of the educational system in the linguistic area, both concerning substitution and normalization processes. After describing the process by which Catalan was introduced in schools in the Balearic Islands, the author analyzes the efects of such introduction upon linguistic competence, the usage of Catalan and the linguistic ideology of Majorcan youths, It is proved that schools has caused an improvement in the degree of linguistic competence of a portion of Majorcan youths but, on the other hand, it does not seem there has a great change in the linguistic ideology or in usage beyond the school environment.